Mastectomy surgery and its influence in the female biopsychosocial scope (Research, Society and Development, 2020)
Objectives: To identify and describe the psychosocial impact on women after mastectomy for the treatment of cancer described in the literature. Methods: This is an integrative review, of a qualitative nature and descriptive, based on Pubmed and the Virtual Health Library: MEDLINE, LILACS and BDENF. The inclusion criteria were: Full texts available for free in the 5-year period (2016-2020). Duplicate materials, in other formats, that did not meet the theme were excluded. 38 articles emerged and after analysis, 24 were used to build the content. Results and discussions: Two thematic categories were identified: Femininity after breast removal; The affective-sexual relationship. Final considerations: It was evidenced that the surgery directly affects the woman, because the breasts in Brazil are culturally appreciated as a sexual and erotic organ. Mastectomy interferes with the woman's biopsychosocial aspect, making it necessary to intervene in various situations in the process of accepting self-image.